Transplantation of embryonic motor neurons into peripheral nerve combined with functional electrical stimulation restores functional muscle activity in the rat sciatic nerve transection model. (30th October 2013) - Kurimoto, Shigeru; Kato, Shuichi; Nakano, Tomonori; Yamamoto, Michiro; Takanobu, Nishizuka; Hirata, Hitoshi
Abstract: Reinnervation of denervated muscle by motor neurons transplanted into the peripheral nerve may provide the potential to excite muscles artificially with functional electrical stimulation (FES). Here we investigated whether transplantation of embryonic motor neurons into peripheral nerve combined with FES restored functional muscle activity in adult Fischer 344 rats after transection of the sciatic nerve. One week after sciatic nerve transection, cell culture medium containing (cell transplantation group, n = 6) or lacking (surgical control group, n = 6) dissociated embryonic spinal neurons was injected into the distal stump of the tibial and peroneal nerves. Electrophysiological and tissue analyses were performed in the cell transplantation and surgical control groups 12 weeks after transplantation, as well as a in naïve control group ( n = 6) that received no surgery. In the cell transplantation group, ankle angle was measured during gait, with and without FES of the peroneal nerve. Ankle angle at mid‐swing was more flexed during gait with FES (26.6 ± 8.7°) than gait without FES (51.4 ± 12.8°, p = 0.011), indicating that transplantated motor neurons in conjunction with FES restored ankle flexion in gait, even though no neural connection between central nervous system and muscle was present. These results indicate that transplantation of embryonic motor neurons into peripheral nerve combined with FES can provide a novel treatment strategy for paralysed muscles. Copyright © 2013 John Wiley & Sons, Ltd.